2008
DOI: 10.1152/ajpgi.00016.2008
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling protein-2 modulates the lipid metabolic response to fasting in mice

Abstract: Sheets AR, Fülöp P, Derdák Z, Kassai A, Sabo E, Mark NM, Paragh G, Wands JR, Baffy G. Uncoupling protein-2 modulates the lipid metabolic response to fasting in mice. Am J Physiol Gastrointest Liver Physiol 294: G1017-G1024, 2008. First published February 21, 2008 doi:10.1152/ajpgi.00016.2008.-Uncoupling protein-2 (UCP2) regulates insulin secretion by controlling ATP levels in ␤-cells. Although UCP2 deficiency improves glycemic control in mice, increased expression of UCP2 interferes with glucose-stimulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…The molecular mechanisms under this effect are not fully understood, but UCP2 KO mice display high expression of lipogenic enzymes, such as FAS, SCD1, and LPL, and decreased expression of CPT1a in WAT (Andrews et al 2010). These data correlate with the higher susceptibility to gain weight in an HFD observed in this model (Joseph et al 2002), as well as with that well-established UCP2-mediated increase in fatty acid oxidation under fasting (Andrews et al 2008, Pecqueur et al 2008, Sheets et al 2008. These data identify UCP2 as a common factor modulating energy homeostasis at hypothalamic (Andrews et al 2008) and peripheral level (Andrews et al 2010).…”
Section: Central Ghrelin Actions On Peripheral Lipid Metabolismmentioning
confidence: 80%
“…The molecular mechanisms under this effect are not fully understood, but UCP2 KO mice display high expression of lipogenic enzymes, such as FAS, SCD1, and LPL, and decreased expression of CPT1a in WAT (Andrews et al 2010). These data correlate with the higher susceptibility to gain weight in an HFD observed in this model (Joseph et al 2002), as well as with that well-established UCP2-mediated increase in fatty acid oxidation under fasting (Andrews et al 2008, Pecqueur et al 2008, Sheets et al 2008. These data identify UCP2 as a common factor modulating energy homeostasis at hypothalamic (Andrews et al 2008) and peripheral level (Andrews et al 2010).…”
Section: Central Ghrelin Actions On Peripheral Lipid Metabolismmentioning
confidence: 80%
“…Exercise can upregulate the hepatic UCP2 mRNA and increase fatty acid β oxidation and decrease body weight and fat mass [15]. In contrast, in UCP2 deficiency, efficient breakdown, conversion, and redistribution of fatty acids were perturbed, then blunted peripheral lipolysis and hepatic lipid were utilized [19]. Our previous study showed that capsaicin significantly increased UCP2 expression in adipose tissue [6].…”
Section: Discussionmentioning
confidence: 99%
“…Since UCP2 can regulate the lipid metabolic response to fasting in mice through the expression of key lipid regulatory enzymes (29,33), we analyzed whether UCP2 regulates lipogenic enzymes in the lipid synthesis pathway in macrophages. Lipid synthesis is regulated by the expression of key lipogenic enzymes, including FASN, acetyl-CoA carboxylase (ACACA), and ATP citrate lyase (ACLY).…”
Section: Ucp2 Regulates Lipid Synthesis Through Fasn In Macrophagesmentioning
confidence: 99%